Association of MicroRNA-652 Expression with Radiation Response of Colorectal Cancer: A Study from Rectal Cancer Patients in a Swedish Trial of Preoperative Radiotherapy - Pathak, Surajit; Meng, Wen-Jian; Sriramulu, Sushmitha; Jothimani, Ganesan; Jangamreddy, Jaganmohan R.; Banerjee, Antara; Ganesan, Alagu Theivanai; Adell, Gunnar; Zhang, Xueli; Sun-Zhang, Alexander; Zhang, Hong; Sun, Xiao-Feng (Current Gene Therapy, 2023)
Background:: Radiotherapy is a standard adjuvant therapy in patients with progressive rectal cancer, but many patients are resistant to radiotherapy, leading to poor prognosis. Our study identified microRNA-652 (miR-652)value on radiotherapy response and outcome in rectal cancer patients. Methods: miR-652expression was determined by qPCR in primary rectal cancer from 48 patients with and 53 patients without radiotherapy. The association of miR-652with biological factors and the prognosis was examined. The biological function of miR-652was identified through TCGA and GEPIA database searches. Two human colon cancer cell lines (HCT116 p53+/+ and p53-/-) were used for in vitro study. The molecular interactions of miR-652and tumor suppressor genes were studied through a computational approach. Results: In RT patients, miR-652expression was significantly decreased in cancers when compared to non-radiotherapy cases (P= 0.002). High miR-652expression in non-RT patients was with increased apoptosis marker (P= 0.036), ATM (P= 0.010), and DNp73 expression (P= 0.009). High miR-652 expression was related to worse disease-free survival of non-radiotherapy patients, independent of gender, age, tumor stage, and differentiation (P= 0.028; HR = 7.398, 95% CI 0.217-3.786). The biological functional analysis further identified the prognostic value and potential relationship of miR-652 with apoptosis in rectal cancer. miR-652expression in cancers was negatively related to WRAP53 expression (P= 0.022). After miR-652inhibition, the estimation of reactive oxygen species, caspase activity, and apoptosis in HCT116 p53+/+ cells was significantly increased compared with HCT116 p53-/- cells after radiation. The results of the molecular docking analysis show that the miR652-CTNNBL1 and miR652-TP53 were highly stable. Conclusion: Our findings suggest the potential value of miR-652expression as a marker for the prediction of radiation response and clinical outcome in rectal cancer patients.
Keywords: prognosis